Public Knowledge of Antibiotic Use at Majlis Taklim Al-Ikhlas East Pontianak: Public Knowledge of Antibiotic Use at Majlis Taklim Al-Ikhlas East Pontianak - Nuruniyah, Nuruniyah (Universitas Muhammadiyah Kalimantan Timur, 2024)
The use of antibiotics, in general, is influenced by user knowledge, so if user knowledge is not correct, it can cause errors in use. Improper use of antibiotics can reduce their effectiveness, which will cause adverse risks such as antibiotic resistance. This study aims to determine the public's knowledge of the use of antibiotics in the Al Ikhlas Taklim council. The results of the study obtained were aged 40-60 years with the number of respondents 21 people having a percentage of 78%, in terms of education level, dominated by university education with a percentage value of 41% for the highest work as many as 11 people (41%) were housewives (IRT), the highest income (≥UMR) as many as 16 people (59.3%), while based on the level of knowledge of respondents who were well categorized as having a percentage of 92.59%. This means there is a correlation between age, the level of education, and the respondent's knowledge of antibiotics knowledge.